(a)Complete the table and by inspection of the table find the solution to the equation m + 10 = 16.
m |
1 |
2 |
3 |
4 |
5 |
6 |
7 |
8 |
9 |
10 |
— |
— |
— |
m + 10 |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
(b) Complete the table and by inspection of the table, find the solution to the equation 5t = 35
t |
3 |
4 |
5 |
6 |
7 |
8 |
9 |
10 |
11 |
— |
— |
— |
— |
— |
5t |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
(c) Complete the table and find the solution of the equation z / 3 = 4 using the table.
z |
8 |
9 |
10 |
11 |
12 |
13 |
14 |
15 |
16 |
— |
— |
— |
— |
z / 3 |
2 2/3 |
3 |
3 1/3 |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
(d) Complete the table and find the solution to the equation m – 7 = 3.
m |
5 |
6 |
7 |
8 |
9 |
10 |
11 |
12 |
13 |
— |
— |
m – 7 |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
— |
Solution:
We will use the concepts of equations to solve this.
(a) For m + 10, the table is represented as below
m |
m + 10 |
1 |
1 + 10 = 11 |
2 |
2 + 10 = 12 |
3 |
3 + 10 = 13 |
4 |
4 + 10 = 14 |
5 |
5 + 10 = 15 |
6 |
6 + 10 = 16 |
7 |
7 + 10 = 17 |
8 |
8 + 10 = 18 |
9 |
9 + 10 = 19 |
10 |
10 = 10 = 20 |
Now, by inspection we may conclude that m = 6 is the solution of the above equation since, for m = 6, m + 10 = 6 + 10 = 16.
(b) For 5t, the table is represented as below
t |
5t |
3 |
5 × 3 = 15 |
4 |
5 × 4 = 20 |
5 |
5 × 5 = 25 |
6 |
5 × 6 = 30 |
7 |
5 × 7 = 35 |
8 |
5 × 8 = 40 |
9 |
5 × 9 = 45 |
10 |
5 × 10 = 50 |
11 |
5 × 11 = 55 |
Now, by inspection we may conclude that t = 7 is the solution of the above equation since, for t = 7, 5t = 5 × 7 = 35.
(c) For z / 3, the table is represented as below
z |
z / 3 |
8 |
8 / 3 = 2 2/3 |
9 |
9 / 3 = 3 |
10 |
10 / 3 = 3 1/3 |
11 |
11 / 3 = 3 2/3 |
12 |
12 / 3 = 4 |
13 |
13 / 3 = 4 1/3 |
14 |
14 / 3 = 4 2/3 |
15 |
15 / 3 = 5 |
16 |
16 / 3 = 5 1/3 |
Now, we may conclude that z = 12 is the solution of the above equation since for z = 12, z / 3 = 12 / 3 = 4.
(d) For m – 7, the table is represented as below
m |
m – 7 |
5 |
5 – 7 = -2 |
6 |
6 – 7 = -1 |
7 |
7 – 7 = 0 |
8 |
8 – 7 = 1 |
9 |
9 – 7 = 2 |
10 |
10 – 7 = 3 |
11 |
11 – 7 = 4 |
12 |
12 – 7 = 5 |
13 |
13 – 7 = 6 |
Now, we may conclude that m = 10 is the solution of the above equation since, for m = 10, m – 7 = 10 – 7 = 3.
Maths NCERT Solutions Class 6 Chapter 11 Exercise 11.5 Question 4
(a)Complete the table and by inspection of the table find the solution to the equation m + 10 = 16. (b) Complete the table and by inspection of the table, find the solution to the equation 5t = 35 (c) Complete the table and find the solution of the equation z / 3 = 4 using the table. (d) Complete the table and find the solution to the equation m – 7 = 3.
Summary:
(a) The solution to the equation m + 10 = 16 is m = 6
(b) The solution to the equation 5t = 35 is t = 7
(c) The solution to the equation z/3 = 4 is z = 12
(d) The solution to the equation m - 7 = 3 is m = 10